2009
DOI: 10.1097/rli.0b013e3181afbb36
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body MRI, Including Diffusion-Weighted Imaging, for the Initial Staging of Malignant Lymphoma

Abstract: Our results suggest that initial staging of malignant lymphoma using whole-body MRI (without DWI and with DWI) equals staging using CT in the majority of patients, whereas whole-body MRI never understaged relative to CT. Furthermore, whole-body MRI mostly correctly overstaged relative to CT, with a possible advantage of using DWI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
79
2
3

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 35 publications
2
79
2
3
Order By: Relevance
“…Other studies have shown that the combination of DWI and T2-weighted imaging is better than T2-weighted imaging alone for the detection of prostate cancer (25,26). Although the use of DWI in other areas is less well established, its utility for primary tumor and metastasis detection and staging in several major cancers is under active investigation (27)(28)(29)(30)(31)(32)(33). Because of its high lesionto-background contrast, the additional value of DWI is expected to lie in the detection of (small) lesions that remain unnoticed on anatomic-based imaging and on functional imaging techniques with low spatial resolution such as SPECT and PET.…”
Section: Clinical Applications and Limitations Of Dwi General Diagnosmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that the combination of DWI and T2-weighted imaging is better than T2-weighted imaging alone for the detection of prostate cancer (25,26). Although the use of DWI in other areas is less well established, its utility for primary tumor and metastasis detection and staging in several major cancers is under active investigation (27)(28)(29)(30)(31)(32)(33). Because of its high lesionto-background contrast, the additional value of DWI is expected to lie in the detection of (small) lesions that remain unnoticed on anatomic-based imaging and on functional imaging techniques with low spatial resolution such as SPECT and PET.…”
Section: Clinical Applications and Limitations Of Dwi General Diagnosmentioning
confidence: 99%
“…Another limitation of DWI is that the evaluation of structures close to the heart, such as mediastinal lymph nodes and the left liver lobe, may be compromised because of signal loss and artifacts due to severe tissue motion (33,(44)(45)(46). Nevertheless, MRI is a versatile imaging modality, and the addition of other sequences may improve the evaluation of the mediastinal lymph nodes (24,47) (Fig.…”
Section: Limitationsmentioning
confidence: 99%
“…Combined 18 F-fluoro-2-deoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) is the standard imaging modality for staging HL, but uses ionizing radiation which is potentially harmful to the unborn fetus [1,2]. Therefore, whole-body magnetic resonance imaging (MRI) was used instead as a radiation-free alternative [2,3]. The whole-body MRI examination, which consisted of coronal T1-weighted and coronal short inversion time inversion recovery (STIR) acquisitions, took 30 min and was well tolerated by the patient.…”
mentioning
confidence: 99%
“…Therefore, whole-body magnetic resonance imaging (MRI) was used instead as a radiation-free alternative [2,3]. The whole-body MRI examination, which consisted of coronal T1-weighted and coronal short inversion time inversion recovery (STIR) acquisitions, took 30 min and was well tolerated by the patient.…”
mentioning
confidence: 99%
“…Their results suggest that in the initial staging of malignant lymphoma, whole-body MRI (with and without DWI) provides similar results in the majority of patients to staging using CT. Indeed whole-body MRI never understaged relative to CT and usually correctly overstaged relative to CT, with a possible advantage of using DWI [2].…”
mentioning
confidence: 99%